2011
DOI: 10.1590/s1806-83242011000500010
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of fluoride dentifrices and varnish on deciduous enamel demineralization

Abstract: The aim of this study was to evaluate the anticaries potential of 500 or 1100 ppm F dentifrices combined with fluoride varnish using a pH-cycling regimen. Seventy primary canines were covered with nail polish, leaving a 4×4 mm window on their buccal surface, and randomly assigned into 7 groups (n = 10): S: sound enamel not submitted to the pH-cycling regimen or treatment; N: negative control, submitted to the pH-cycling regimen without any treatment; D1 and D2: subjected to the pH-cycling regimen and treated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
(22 reference statements)
1
20
0
1
Order By: Relevance
“…This feature might be attributed to remaining CHX particles around negatively ionized tooth surfaces with regular tooth brushing (1,7,8,10,23). This study also confirmed that one-visit application of CHX-based varnishes (Group 1) showed better antimicrobial properties over the fluoride (Group 3) varnish treatments, as previously described (8,10,11). The limited/biased factor of Group 2 should also be taken into account, as it had a potential advantage since the home-based self-application of Cervitec®Gel could increase treatment success over professionally applied varnishes in terms of providing acceptable oral hygiene features.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This feature might be attributed to remaining CHX particles around negatively ionized tooth surfaces with regular tooth brushing (1,7,8,10,23). This study also confirmed that one-visit application of CHX-based varnishes (Group 1) showed better antimicrobial properties over the fluoride (Group 3) varnish treatments, as previously described (8,10,11). The limited/biased factor of Group 2 should also be taken into account, as it had a potential advantage since the home-based self-application of Cervitec®Gel could increase treatment success over professionally applied varnishes in terms of providing acceptable oral hygiene features.…”
Section: Discussionsupporting
confidence: 90%
“…Chlorhexidine and thymol (Cervitec®Plus) combination as a varnish treatment was found to be beneficial in inhibiting salivary MS levels and reducing gingivitis therefore improves oral hygiene in orthodontic patients (8,9-11). Chlorhexidine-based toothpastes as an adjunct to mechanical cleaning facilitate the removal of plaque and providing better oral hygiene in orthodontic patients (1,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teeth were submitted to the formation of artificial caries by pH cycling [14] keeping the teeth in demineralizing solution (CaCl 2 2.2 mM, NaH 2 PO 4 2.2 mM, and acetic acid 0.05 M; pH of 4.5, adjusted with KOH 1 M; 15 mL per tooth) for 3 hours and in remineralizing solution (CaCl 2 1.5 mM, NaHPO 4 0.9 mM, and KCl 0.15 mM; pH of 7.0; 15 mL per tooth) for 20 hours. All the teeth were briefly washed in deionized water between solutions and placed in artificial saliva for 30 minutes at the end of the demineralization process and for 30 minutes at the end of the remineralization process (CaCl 2 (15 mg), MgCl 2 (5 mg), KCl (0.1 g), KSCN (10 mg), Na 2 HPO 4 (40 mg), sodium carboxymethylcellulose (1.0 g), methylparaben (0.1 g), and water (1 L); pH of 7.0).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a white 5% NaF varnish containing fTCP has been introduced in the market (Clinpro White, 3M corp., St. Paul, MN, USA). The use of pH cycling and enamel microhardness has been shown to be a useful in vitro tool to assess the protective effect of fluorides [14, 15]. …”
Section: Introductionmentioning
confidence: 99%